2020
DOI: 10.3390/jcm9103205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Apical Periodontitis and Metabolic Syndrome and Cardiovascular Events: A Cross-Sectional Study

Abstract: Aim: Both apical periodontitis (AP) and metabolic syndrome (MetS) are associated with atherosclerotic cardiovascular disease (ACVD), the main cause of cardiovascular events. The aim of this study was to investigate the prevalence of AP and the oral inflammatory burden in control subjects and patients suffering cardiovascular events, analyzing the possible association between AP and the oral inflammatory burden with MetS. Materials and Methods: Using a cross-sectional design, 83 patients suffering a cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…A retrospective evaluation of the CT scans of 531 patients reported that CAP was positively correlated with atherosclerotic lesions (Petersen et al, 2014 ). The number of teeth affected by CAP is significantly associated with cardiovascular events (Gonzalez‐Navarro et al, 2020 ). In a cross‐sectional study that included 120 men between the ages of 20 and 40 who did not have CVD, periodontal disease, traditional cardiovascular risk factors and impaired flow‐mediated dilatation, elevated carotid intima‐media thickness was found in subjects with CAP, which indicates a possible association between dental pulp infection and CVD (Chauhan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective evaluation of the CT scans of 531 patients reported that CAP was positively correlated with atherosclerotic lesions (Petersen et al, 2014 ). The number of teeth affected by CAP is significantly associated with cardiovascular events (Gonzalez‐Navarro et al, 2020 ). In a cross‐sectional study that included 120 men between the ages of 20 and 40 who did not have CVD, periodontal disease, traditional cardiovascular risk factors and impaired flow‐mediated dilatation, elevated carotid intima‐media thickness was found in subjects with CAP, which indicates a possible association between dental pulp infection and CVD (Chauhan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of this study are part of the growing interest in research on the possible relationship of endodontic pathology with systemic diseases. The results of epidemiological studies carried out in the last years suggest a link between AP and some systemic diseases, such as diabetes mellitus (López‐López et al, 2011; Sánchez‐Domínguez et al, 2015), cardiovascular diseases (Cotti & Mercuro, 2015), atherosclerosis (Berlin‐Broner et al, 2017), tobacco smoking (López‐López et al, 2012; Pinto et al, 2020), metabolic syndrome (González‐Navarro et al, 2020), osteoporosis (López‐López et al, 2015), inherited coagulation disorders (Castellanos‐Cosano et al, 2013), and others (Segura‐Egea et al, 2015). The results of these studies are already notable for the simple fact that they draw the attention of physicians and dentists to the interrelation between oral inflammatory pathology and systemic health status.…”
Section: Discussionmentioning
confidence: 99%
“…There is a low‐to‐moderate evidence in the literature that apical periodontitis can exert systemic effects in the host and predispose to systemic diseases (Berlin‐Broner et al, 2017; Caplan et al, 2006; Cotti et al, 2011; Cotti & Mercuro, 2015; Garrido et al, 2019; Gonzalez‐Navarro et al, 2020; Joshipura et al, 2006; Pasqualini et al, 2012; Segura‐Egea et al, 2015). So far, there is no scientific reason to regard endodontic infections as segregate events that have no effects on other body sites.…”
Section: Future Directionsmentioning
confidence: 99%